Aktivitas Antioksidan dan Kadar Vitamin C Daging Buah dan Sirup Buah Naga (Hylocereus costaricensis) - Titin Aryani; Isnin Aulia Ulfah Mu’awanah (Biomedika, 2019)
Research on antioxidant activity and vitamin C levels of dragon fruit and Hylocereus costaricensis dragon fruit syrup from Kulon Progo has been conducted. The purpose of this study was to study the antioxidant activity and levels of vitamin C in dragon fruit meat and dragon fruit syrup from Kulon Progo. The sampling method is done by purposive sampling method. The method of measuring antioxidant activity using DPPH (1,1-Diphenyl-2-picryl Hidrazil) immersion method was measured with a wavelength of 517 nm. The method of determining the level of vitamin C is carried out by the method of titration of Iodimetry using a standard solution of iodine. The results showed that the average antioxidant activity of dragon fruit was 67.81%, whereas in dragon fruit syrup was 42.81%. While the level of vitamin C in dragon fruit is 12.65% while in dragon fruit syrup is 3.667%. Can reduce the levels of antioxidants and vitamin C levels of dragon fruit higher than dragon fruit syrup.